Zapornik v Mariboru, prostozidar in nobelovec - Premzl, Primož (Časopis za zgodovino in narodopisje, 2024)
The article discusses political prisoners from the beginning of World War I, with an emphasis on Ivo Andrić, who served his sentence in the prison in Melje, Maribor. Among them, some were Freemasons while serving their sentences, and most of them became Freemasons during the time of the Kingdom of Yugoslavia. Josip Broz Tito who is still speculated to this day to have been a Freemason, is also mentioned as a political prisoner in Maribor. Branko Šömen, who in the 1990s became one of the key figures in the modern history of Freemasonry in Slovenia and Croatia with an exceptional Freemasonry bibliography, also served a short sentence in Maribor as a political prisoner in communist Yugoslavia.
Keywords: biografije; biographies; Freemasons; Ivo Andrić; Maribor; political prisoners; politični zaporniki; prostozidarji